2017
DOI: 10.1115/1.4036096
|View full text |Cite
|
Sign up to set email alerts
|

Design and Numerical Analysis of Vibration Isolators With Quasi-Zero-Stiffness Characteristics Using Bistable Foldable Structures

Abstract: In this paper, a novel vibration isolator based on a foldable cylinder with a torsional buckling pattern, which is also called Kresling's pattern, is proposed, and the performance of the proposed isolator in terms of preventing structural vibration is numerically evaluated. It is known that foldable cylinders with a torsional buckling pattern provide bistable folding motions under specific conditions. For simplification, a foldable cylinder with a torsional buckling pattern is modeled using horizontal, longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The results revealed that the intra and inter‐well dynamics of the bistable stacked Miura‐ori are strongly influenced by the asymmetry in its force‐deformation relationship. A cylindrical truss structure inspired by the Kresling folding pattern were investigated for vibration isolation both numerically and experimentally . This vibration isolation function stemmed from a quasi‐zero stiffness (QZS) property obtained by integrating a linear spring with the bistable Kresling pattern.…”
Section: Folding Induced Mechanical Propertiesmentioning
confidence: 99%
“…The results revealed that the intra and inter‐well dynamics of the bistable stacked Miura‐ori are strongly influenced by the asymmetry in its force‐deformation relationship. A cylindrical truss structure inspired by the Kresling folding pattern were investigated for vibration isolation both numerically and experimentally . This vibration isolation function stemmed from a quasi‐zero stiffness (QZS) property obtained by integrating a linear spring with the bistable Kresling pattern.…”
Section: Folding Induced Mechanical Propertiesmentioning
confidence: 99%
“…As θ is between 0 and 1 and U r ðX Þ is less than 0.1 in equation ( 9), the cosine and sine terms in equation ( 9) can be replaced by their first-order Taylor expansion, which gives equation (10) without introducing significant error.…”
Section: Force-displacement Response and Maximum Strainmentioning
confidence: 99%
“…These elements are designed so that overall stiffness of the system was close to zero when imposed with the gravity load of the isolating mass. 2 Researchers are continuously exploring new and better mechanisms to achieve the QZS, including the folded pendulum or X-pendulum, [3][4][5] magnetic ant-springs, 2,6,7 anti-springs based on geometric nonlinearity, [8][9][10][11][12][13][14][15] Euler buckling beams, 16,17 and the bistable structures. 18 In addition to the requirement of the stiffness and loading capacity, there are often limitations on overall weight of the isolator, especially when the isolator is used in aerospace engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Fulcher et al [19] developed a kind of QZS system using buckled beams to generate a negative stiffness. Ishida et al [20] presented a prototype vibration isolator based on a foldable cylinder with a torsional buckling pattern for the negative stiffness. Lan et al [21] designed a special planar spring to manage a wide range of loads and the QZS system had a better vibration isolation performance compared with linear isolators.…”
Section: Introductionmentioning
confidence: 99%